Seletividade de herbicidas e avaliação agronômica de sorgo sacarino no semiárido - Moura, Joana Gomes de (2017)
The increase in the demand for ethanol contributes to sweet sorghum emerging as an important alternative in the generation of biomass for the production of this biofuel, mainly in the sugar cane harvest. However, one of the main problems in sorghum cultivation has been the management of weeds that is hampered by the lack of selective herbicides for the crop. Therefore, the objective of this work was to evaluate the behavior of sorghum genotypes submitted to chemical weed control. The sorghum genotypes used were BRS 506, BRS 511 and SF 15, submitted to weed management, with a mixture of the following treatments: atrazine + nicosulfuron (2.500 + 50 g ha-1), (2.500 + 40 g ha-1), (2.500 + 30 g ha-1), (2.500 + 20 g ha-1), (2.500 + 10 g ha-1) and no control. The experiment was carried out in an experimental area of the Curu Valley Farm of the Federal University of Ceará, Pentecoste – CE. The experimental design was randomized blocks, in a 3 x 6 factorial scheme, with four replications. Fresh and dry biomass production (leaf, panicle and stem) and yield related traits (yield, weight, density, total soluble solids, total soluble carbohydrate content and estimated ethanol production) were evaluated. Data were submitted to analysis of variance, mean comparison test and regression. The doses of 30 and 40 g ha-1 of nicosulfuron in mixture with atrazine were selective for the crop and resulted in high yield of sweet sorghum. The results show that the genotypes BRS 506 and BRS 511 have a high potential for cultivation, due to the higher yield both in the characteristics related to the phytomass production and in the variables related to the ethanol production.